PERANCANGAN DAN PEMBUATAN ALAT SANGRAI KOPI OTOMATIS MENGGUNAKAN ARDUINO UNO DILENGKAPI DENGAN TIMER: Yandy Kurniawan Syah1), Alvin Zuhair, M.T2), Devis Yusofa, M.Pd.3), Mukhlison, S.T., M.T4), Sri Widoretno, S.T., M.T5) - Alvin (Universitas Islam Balitar Blitar, 2024)
Kedawung Village is one of the villages that produces coffee with traditional processing. This process has several disadvantages, including requiring a lot of labor because the coffee must be constantly stirred, and the processing process takes a long time. To overcome this problem, researchers developed an automatic coffee bean roaster based on Arduino Uno. This tool is designed to produce coffee with traditional flavors but with a modern, practical, and economical roasting system. The purpose of this research is to develop the design of an automatic coffee bean roaster based on Arduino Uno. Knowing the working system of the Arduino Uno-based automatic coffee bean roaster. The development of an Arduino-based automatic coffee bean roaster consists of two main components, namely hardware development and software development. The working system of this tool still uses a combination of a heating system using a portable stove and a roasting system, with temperature control using an automation system. With this tool, it is expected that the process of roasting coffee beans can become more efficient and practical, so as to improve the quality of coffee production in Kedawung village and reduce the workload of coffee farmers in the processing process.